Sounds and Natures Do Often Agree: Prediction of Esports Players’ Performance in Fighting Games Based on the Operating Sounds of Game Controllers - Yamato Hiratsuka; Kazuki Kuga; Takahiro Miura; Tetsuo Tanaka; Mari Ueda (Applied Sciences)
In research focusing on esports, studies have been conducted on designs that attract competitors, performance estimation, training methods, and motivational factors. However, quantitative and convenient methods for performance evaluation are still in the development stage among the numerous performance evaluation methods. In particular, few method has been developed to objectively measure an individual’s mental state utilizing limited equipment. It has been observed that when players’ performance deteriorates or they are under pressure, they occasionally operate the controller in accordance with their state, resulting in the sound of the controller increasing. Therefore, this study aimed to clarify the relationship between the sound of esports players’ controller operations and their objective as well as subjective metrics, including their emotional state and performance during the game. Initially, the controller sounds of players of various ranks in Super Smash Bros. Ultimate (SSBU) by Nintendo were explored, aiming to elucidate the connection between the operation sounds of adept and intermediate esports competitors and their day-to-day fluctuations in game performance and emotional well-being. The findings revealed a discernible pattern: the more proficient the player, the more resonant the sounds emanating from their controller during gameplay. Furthermore, the operational sounds of skilled players exhibited an escalation when their performance faltered.